Fatores álgicos relacionados à instalação de implantes dentários : uma avaliação de 7 dias - Rizzatto, Laura Vitória (2020)
To compare the intensity of pain reported by the patient in t h e f ir st seven days after the installation of osseointegrated dental implants with surgical factors, gender and age of the patients. Materials and methods: The sample consisted of 108 patients from the Faculty of Dentistry of UPF between 2018 and 2019. All patients underwent clinical evaluation and radiographs before the implants installation. The variables torque, pre and postoperative medication, cicatrization of first or second intention, gender, age, number of quadrants, number of implants and type of surgery were related to the pain outcome, recorded from the first until the seventh day after surgery. The instrument for assessing pain was a visual analog scale (VAS). Data was analyzed as an average of pain for all postoperative days. To assess the relationship between pain and the predictor variables, univariate Poisson regression models were use. Rate ratios were obtained with 95% confidence intervals. Results: General pain was reported as moderate / severe (VAS: 3 -10) by 30.56% of patients, mild pain (VAS: 1-3) by 55.56% of patients, and did not report any painful symptoms 13.89% of patients. Patients who adhered to the anti-inflammatory m edicat io n protocol showed less pain compared to patients who did not followed the protocol (p = 0.01). Individuals with implants installed with high torques (50 - 80N) showed more pain (p = 0.03) compared to patients with implants in st alled with low (0-25N) and medium torques (30-45N). The other factors evaluated were not significant. Conclusion: Torque was the most relevant factor among all evaluated. High torques generate greater pain than smaller torques. The factors gender, age, number of quadrants, number of implants, type of surgery and pre- and postoperative analgesics did not interfere on the patient's pain.